COMPARISON IDENTIFICATION OF GEOMORPHIC FLOOD INDEX METHOD AND PAIRWISE COMPARISON METHOD ON FLOOD PRONE AREA DETERMINATION IN EAST BORNEO - Fitri Amalia, Annisa
During 2022, Badan Nasional Penanggulangan Bencana (BNPB, 2022) recorded that floods have occurred 1,524 times out of a total of 3,531 disasters that occurred in Indonesia. The province of East Kalimantan is ranked 20th out of 35 provinces in Indonesia that frequently experiences flood, with the total of 28 occurrences during 2022. Floods that occurred in East Kalimantan in 2022 have caused two fatalities. Therefore, the problem must be addressed quickly so it will not cause casualties in the future. This undergraduate thesis is created to indicate flood-prone areas in East Kalimantan Province. After obtaining a map of flood-prone areas from various methods, the methods were analyzed to indicate, which method is more effective for mapping flood-prone areas. The methodology used in this research consists of literature study, sample data collection in the form of questionnaires addressed to the government and academics who are experts in the field of floods as weighting material for the Pairwise Comparison method, and mapping flood-prone areas using two methods, which are the Geomorphic Flood Index (GFI) and the Pairwise Comparison. The results obtained from this study are maps of flood-prone areas in East Kalimantan Province from the two methods, recommendations of the more efficient method for identifying flood-prone areas, and recommendations for flood mitigation based on the results of this study. This research is expected to be used as a reference to determine the best method for identifying flood-prone areas and to consider policy formulation to reduce the impact of floods in East Kalimantan Province.